2011
DOI: 10.1021/ct2005159
|View full text |Cite
|
Sign up to set email alerts
|

Structural Stability of V-Amylose Helices in Water-DMSO Mixtures Analyzed by Molecular Dynamics

Abstract: Computational techniques have been employed to fundamentally understand the behavior of helically structured amylose in water/DMSO mixtures. Using a computationally generated amylose helix of 55 glucose residues, we have investigated the time-dependent behavior of intra- and intermolecular hydrogen bonds, particularly between O2 and O3 of adjacent glucose molecules and between O6 and neighboring O2 and O3 groups. The helix character was defined by the total number of residually existing hydrogen bonds. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 52 publications
4
48
0
Order By: Relevance
“…As observed in experimental data and corroborated further by MD studies, inter-and intra-molecular interactions play a major role on the molecular behavior of complex systems comprised by natural plasticizers and polysaccharides [12,[17][18][19]21] . In fact, they are essential for the rational design of high performance biomaterials as well as to predict its properties.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…As observed in experimental data and corroborated further by MD studies, inter-and intra-molecular interactions play a major role on the molecular behavior of complex systems comprised by natural plasticizers and polysaccharides [12,[17][18][19]21] . In fact, they are essential for the rational design of high performance biomaterials as well as to predict its properties.…”
Section: Introductionsupporting
confidence: 72%
“…They found that strong hydrogen bonding was essential for cohesion of the amylose/glycerol model, which was further corroborated by experimental data (X-ray diffraction, tensile strength and water uptake), probed with starch/glycerol cast films. Tusch et al [18] observed that at certain simulation times the helix character of a single helical amylose chain (55 monomeric units) in water/DMSO mixtures was stabilized after increasing the DMSO concentration, since DMSO helps to preserve intramolecular hydrogen bonds in starch. Their findings were in consonance with NMR data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,[20][21][22] However, previous MD studies of amylose have mainly dealt with small amylose fragments in water or studies of V-amylose in low polarity solvents. [23][24][25] The object of the present study was to deepen the understanding of the structure and formation of V-amylose inclusion complexes in view of its anticipated use as a delivery system of long chain fatty acids and other nutraceuticals. To that aim, we consider a short amylose fragment, and simulate its structure and dynamics in the presence of either dipalmitoyl-phosphatidylcholine (diC 16 -PC) or glycerol monooleate (GMO) in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers have reported various properties of amylose such as structural conformation and stability in solvents (Nakanishi et al 1993;Shimada et al 2000;Radosta et al 2001;Tusch et al 2011), conformational transitions (Cheetham & Tao 1997), crystallisation and crystal structure (Takahashi et al 2004;Creek et al 2006;Popov et al 2009;Montesanti et al 2010), amylose complexes (Hulleman et al 1996;Ozcan & Jackson 2002;Nuessli et al 2003;Ciesielski & Tomasik 2004;Cardoso et al 2007;Nishiyama et al 2010), gel microstructure and textural properties (Torres et al 1978;Leloup et al 1992) and amylose gel physical network (Lay & Delmas 1998). Whereas, research on the properties of amylopectin was focused on its structural and retrogradation properties (Manners & Matheson 1981;Manners 1989;Paredes-Lopez et al 1994), crystallinity of amylopectin films and network formation (Putaux et al 2000;Myllarinen et al 2002), and amylopectin complexes (Ciesielski & Tomasik 2004).…”
mentioning
confidence: 99%